Internalization of Islamic Education Values in Establishing Student Social Characters - Ririn Nuraini; Ika Wahyu Susiani (Aqlamuna: Journal of Educational Studies, 2023)
Students are the next generation of the nation who must be equipped with a lot of knowledge. Education in tertiary institutions should be able to motivate them to develop their potential properly. In addition, they must also be equipped with insight on how to live in society and care for the surrounding environment. However, in reality efforts to build student character are still considered not more important than other educational materials. Thus, until now it is common to find college graduates who experience social shock when they are involved in society. Character formation can be used as an alternative solution in solving these problems. In this case the values ​​of Islamic education and social character play a very dominant role in social life. This study uses a qualitative approach to the type of field research. The data collection process uses in-depth interviews, participatory observation and documentation. This study aims to find out how the strategy of instilling the values ​​of Islamic education in tertiary institutions to students and the implications for the social character of students. The results of this study indicate that the strategy of instilling the values of Islamic education in shaping the social character of students in the Islamic Religious Education study program at the Riyadlotul Mujahidin Ngabar Ponorogo Islamic Education Study Program is by realizing the curriculum by combining theoretical and practical aspects (daily life). Which is manifested in an integrated manner through: 1) Exemplary Method, 2) Habituation Method, 3) Giving Advice, 4) Giving Attention, and 5) Giving Sanctions. The impact of the strategy of instilling Islamic educational values in shaping the social character of students in the Islamic Religious Education study program at the Riyadlotul Mujahidin Ngabar Ponorogo Islamic Institute has a positive impact. This is evidenced by changes in behavior in the social life of students in a better direction.